Manejo de inventarios con la utilización del Método Just In Time en el Centro de Atención y Formación a niños niñas adolescentes y adultos Carlos Luis Morales Reyna. - Suarez Herrera, Alex Omar (2024)
Inventory management is the storage of a group of products awaiting further processing. more or less close to employment, which allows them to be supplied regularly to those who consume them without imposing interruptions or possible delays in the production process Supply from suppliers, important for organizations that do not have good inventory management in warehouses of different companies in the Ecuador. Therefore, this study is carried out to provide solutions to various problems companies know when to replenish or purchase products and effective inventory management ensures that the company has enough products. To meet the needs of consumers, on the other hand, the current research objectives evaluate inventory management and control, its adaptation to just-in-time methods and its J&F Inversiones S.A.C Profit and Loss Statement 2018, incl. An organization dedicated to the steel sales industry, this is a survey, the quantitative approach is used because the analysis is carried out on the income statement, Simulation of just-in-time methods. Finally, the simulation of the Just in Time method will be carried out. This has a positive effect on the company's inventory management, as it will reduce its inventory to zero inventories, zero spaces and minimize losses due to obsolete supplies. Its profitability is expected to increase by 100%.